(untitled) (Bangladesh Journal of Medical Science, 2025)
Background Polycystic ovary syndrome(PCOS) is a frequently prevalent health issue that significantly affects women’s reproductive health. The prompt diagnosis and suitable treatment methods employed by medical professionals determine favorable clinical outcomes of the disease. Objective The present study aimed to explore physicians’ agreement with the standard guidelines for PCOS diagnosis and treatment. Methods The cross-sectional study was conducted using a selfadministered 36-item questionnaire at four public and three private tertiary care hospitals and different clinics in Karachi, Pakistan. Results The overall response rate of the present study was 77.3%, with a mean age of 36.1±11.9 years. The Rotterdam criteria were the most commonly used measure for the diagnosis of PCOS by (n=112, 71.3%) respondents; however, the response rate varied significantly with their experience (p<0.001). Lifestyle modifications (n=149, 94.9%) and metformin (n=142, 90.4%) were the treatments most commonly prescribed by the respondents. Almost all the respondents (n=150, 95.5%) consider obesity, infertility, and hirsutism when prescribing hormonal medications for PCOS. Conclusions The outcomes revealed a disparity in the diagnostic approaches of PCOS among the respondents. The findings can be used to establish strategies to raise knowledge among primary care physicians, shorten the time it takes to diagnose cases, and, ultimately, better manage women who have the condition. Bangladesh Journal of Medical Science Vol. 24 No. 01 January’25 Page : 230-238